2020
DOI: 10.1136/bcr-2019-232890
|View full text |Cite
|
Sign up to set email alerts
|

Rare case of bilateral wrist and foot drop from SLE-related vasculitic polyneuropathy

Abstract: Systemic lupus erythematosus (SLE) is a heterogeneous, chronic, inflammatory, autoimmune disease characterised by multiorgan involvement and the production of multiple autoantibodies. Neurological manifestations in SLE patients are frequently reported—the prevalence is 37%–90%. We present a unique case where the patient presented with bilateral wrist and foot drop for 4 days, which later led to the diagnosis of SLE-related vasculitic polyneuropathy. During the course of treatment, the patient received predniso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Our patient's progress was very satisfactory under treatment with hydroxychloroquine combined with prednisone (which are first-line molecules and more accessible in our context), the literature describes good functional recovery under treatment [15,16].…”
Section: Discussionmentioning
confidence: 62%
“…Our patient's progress was very satisfactory under treatment with hydroxychloroquine combined with prednisone (which are first-line molecules and more accessible in our context), the literature describes good functional recovery under treatment [15,16].…”
Section: Discussionmentioning
confidence: 62%
“…For patients with fertility requirements, it has been reported that rituximab combined with adequate corticosteroid therapy can also achieve good results. 54 The present review of cases suggests that patients with SLE and CIDP respond well to corticosteroids and immunosuppressive therapy and that the early damage is reversible. The timely diagnosis and treatment of patients is therefore essential, and can significantly improve patient prognosis.…”
Section: Discussionmentioning
confidence: 80%